Oral Versus Intravenous Antibiotics for Pediatric Osteoarticular Infection: When and to Whom?. Issue 9 (27th June 2022) - Alcobendas Rueda, Rosa M.; Núñez, Esmeralda; Martín, Laura; Hernández, María Belén; Saavedra-Lozano, Jesús; Udaondo, Clara; Murias, Sara; Remesal, Agustin; Calvo, Cristina; ,
Abstract : Background: Osteoarticular infections (OAIs) are typically treated initially with intravenous antibiotics. The objective of this study was to evaluate whether an exclusive oral treatment in selected children may be appropriate. Methods: The Spanish Network of Osteoarticular Infections is a nationwide multicenter registry comprising 37 hospitals in Spain. The registry prospectively includes clinical characteristics and outcome of children with OAI. One of the hospitals from RioPed offers oral treatment to children meeting certain criteria. Patients were classified into 2 groups. Group 1: management with initial intravenous antibiotic therapy. Group 2: patients exclusively treated with oral antibiotics. A comparison between the 2 groups was performed. Results: We compared 893 children who initially received intravenous antibiotics (group 1) with 64 children who received exclusively oral therapy (group 2). Patients from group 2 were younger (33.9 vs. 20.3 months; P = 0.001), had a lower percentage of Staphylococcus aureus (23.3% vs. 3.1%; P < 0.001), a higher proportion of Kingella kingae (12.1% vs. 28.1%; P = 0.001), higher erythrocyte sedimentation rate/C-reactive protein (CRP) ratio (1.4 interquartile range 0.6–3.6 vs. 3.3 interquartile range 1.7–5.7; P < 0.001) and showed lower rate of fever (63% vs. 48.8%; P = 0.024) than in group 1. Complications were not found in group 2. Conclusions: An exclusively oral administration could be a safe option in selected patients with OAI. Low-risk criteria are proposed: good general condition, no underlying disease, 6 months to 3 years old, appropriate oral tolerance, C-reactive protein <80 mg/L, erythrocyte sedimentation rate/C-reactive protein ratio ≥0.67, no skin injury, no recent surgery, no cervical spondylodiscitis and no local complications at onset.